2015
DOI: 10.3233/cbm-140432
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive significance of thymidylate synthase protein expression in non-small cell lung cancer: A systematic review and meta-analysis

Abstract: Low TS protein expression is a favorable predictive factor for better OS/PFS in NSCLC patients treated with TS-targeted drugs. Prognostic value of TS protein expression needs further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Despite major advances in therapeutic strategies, the prognosis for NSCLC patients remains poor; the 5-year survival rate is less than 15% 2 . A growing number of molecular alterations and specific gene expression signatures have been implicated in NSCLC carcinogenesis, including KRAS , EGFR mutations, EML4-ALK rearrangements, and VEGF and thymidylate synthase expression levels, among others 35 . However, the detailed molecular pathogenesis of NSCLC is far from fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Despite major advances in therapeutic strategies, the prognosis for NSCLC patients remains poor; the 5-year survival rate is less than 15% 2 . A growing number of molecular alterations and specific gene expression signatures have been implicated in NSCLC carcinogenesis, including KRAS , EGFR mutations, EML4-ALK rearrangements, and VEGF and thymidylate synthase expression levels, among others 35 . However, the detailed molecular pathogenesis of NSCLC is far from fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta‐analysis, Liu et al . reported that TS expression had prognostic value in NSCLC patients who received TS inhibitor treatment …”
Section: Introductionmentioning
confidence: 99%
“…More than 80% of lung cancer are non-small cell lung cancer (NSCLC) (2,3). In China, the incidence of lung cancer in the past few decades has doubled due to the aging population, smoking and decline in air quality (4).…”
Section: Introductionmentioning
confidence: 99%